Scalable and practical synthesis of clickable Cu-chelating azides. Issue 56 (9th June 2017) - Sallustrau, A.; Bregant, S.; Chollet, C.; Audisio, D.; Taran, F.
Abstract : A convenient synthetic access to chelating azides enabled the preparation of efficient clickable fluorescent derivatives. The comparison of their reactivity to regular azides showcased the superiority of such derivatives for labeling applications. Abstract : A convenient and effective synthetic access to chelating azides was designed enabling the preparation of efficient clickable fluorescent derivatives. The comparison of the reactivity of these chelating azides to regular azides showcased the striking superiority of such derivatives for labeling applications.